VD_FINDINFO Pron / 2009 / 58 vom 11. November 2009 - VD Tribunal cantonal (2009)
DÉCISION D'IRRECEVABILITÉ, REPRÉSENTATION, REPRÉSENTATION SANS POUVOIRS | 17 CPC, 461 CPC, 464 al. 2 CPC, 62 CPC, 68 CPC, 69 CPC, 71 CPC